Lipidomic analysis of mesenchymal cells candidates for cell therapy - Campos, Ana Margarida Ferreira (2015)
Mesenchymal stromal cells are adult stem cells found mostly in the bone marrow. They have immunosuppressive properties and they have been successfully applied as biological therapy in several clinical trials regarding autoimmune diseases. Despite the great number of clinical trials, MSCs’ action is not fully understand and there are no identified markers that correlate themselves with the immunomodulatory power. A lipidomic approach can solve some of these problems once lipids are one of the major cells’ components. Therefore, in this study cells’ lipidome was analysed and its deviations were evaluated according to the medium of culture and to the presence of pro-inflammatory stimuli, mimicking physiological conditions in which these cells are used. This was the first study ever made that aimed to analyse the differences in the phospholipid profile between mesenchymal stromal cells non-stimulated and stimulated with proinflammatory stimulus. This analysis was conducted in both cells cultured in medium supplemented with animal serum and in cells cultured in a synthetic medium. In cells cultured in the standard medium the levels of phosphatidylcholine (PC) species with shorter fatty acids (FAs) acyl chains decreased under pro-inflammatory stimuli. The level of PC(40:6) also decreased, which may be correlated with enhanced levels of lysoPC (LPC)(18:0) - an anti-inflammatory LPC - observed in cells subjected to TNF-α and IFN-γ. Simultaneously, the relative amounts of PC(36:1) and PC(38:4) increased. TNF-α and IFN- γ also enhanced the levels of phosphatidylethanolamine PE(40:6) and decreased the levels of PE(38:6). Higher expression of phosphatidylserine PS(36:1) and sphingomyelin SM(34:0) along with a decrease in PS(38:6) levels were observed. However, in cells cultured in a synthetic medium, TNF-α and IFN-γ only enhanced the levels of PS(36:1). These results indicate that lipid metabolism and signaling is modulated during mesenchymal stromal cells action.